Malta: the erotic of the Island in the fiction of Eça de Queiroz - Vilela, Ana Luísa (2021)
The island of Malta has fueled the imagination of the nineteenth century writer greatest Portuguese novelist, Eca de Queiroz (1845-1900).In The Mystery of Sintra Route, the island of Malta is the setting of a story of love and crime which mixes humour, romanticism and one of the most unforgettable portraits of a female character.